2010
DOI: 10.1074/jbc.m110.123406
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions and Electrolytes Regulate the Dissociation of Heme from Human Hemopexin at Physiological pH

Abstract: The stability of the hemopexin-heme (Hx-heme) complex to dissociation of the heme prosthetic group has been examined in bicarbonate buffers in the presence and absence of various divalent metal ions. In NH 4 HCO 3 buffer (pH 7.4, 20 mM, 25°C) containing Zn 2؉ (100 M), 14% of the heme dissociates from this complex (4.5 M) within 10 min, and 50% dissociates within 2 h. In the absence of metal ions, the rate of dissociation of this complex is far lower, is decreased further in KHCO 3 solution, and is minimal in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In fact, recently Byrne et al [24] identified an anion-binding site that regulates iron dissociation from the transferrin protein implicating increasing Cl À concentrations, in addition to a lower pH, as key regulators of transferrin function in the early endosome. In addition to the orthodoxy of the cation-dependent and cation-independent mannose-6-phosphate receptors [25], ionic modulation of receptor-ligand interactions has also been reported for hemopexin-heme [26], LDLR-LDL [27], and CD163-haptoglobin-hemoglobin [28]. Furthermore, apart from affecting receptor sorting, changes in the luminal ions could impact on the degradative pathway.…”
Section: Endosomal Electrolytes Directly Modulate Endosomal Protein Fmentioning
confidence: 97%
“…In fact, recently Byrne et al [24] identified an anion-binding site that regulates iron dissociation from the transferrin protein implicating increasing Cl À concentrations, in addition to a lower pH, as key regulators of transferrin function in the early endosome. In addition to the orthodoxy of the cation-dependent and cation-independent mannose-6-phosphate receptors [25], ionic modulation of receptor-ligand interactions has also been reported for hemopexin-heme [26], LDLR-LDL [27], and CD163-haptoglobin-hemoglobin [28]. Furthermore, apart from affecting receptor sorting, changes in the luminal ions could impact on the degradative pathway.…”
Section: Endosomal Electrolytes Directly Modulate Endosomal Protein Fmentioning
confidence: 97%
“…Indeed, substitution of Mg 2+ affects the LHCII and the photosystem PSII, thereby causing a decrease in photosynthesis ( 20 ). Likewise, it was shown that Ni 2+ , Cu 2+ , and Zn 2+ induced a destabilization of heme binding to b -type hemoproteins and led to the release of heme from myoglobin, ferricytochrome b 5 , indoleamine-dioxygenase, hemopexin, and cytochrome P450 ( 45 , 46 ). Formation of a bioconjugate of human hemoglobin with Ag + ions was also reported ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…48 Other chemical modifications have been reported for human hemopexin, for example, exposure of hemopexin to Ni 2þ can result in hydrolysis of a susceptible peptide bond in the linker sequence. 68 Carbonylation of hemopexin has been detected in patients with sporadic Alzheimer's disease 69 and with idiopathic pulmonary fibrosis. 70 Although the cause of this oxidation remains unknown, it raises the possibility that hemopexin could also be susceptible to oxidation under the conditions of some purification protocols.…”
Section: Potential Chemical and Structural Modification Of Hemopexinmentioning
confidence: 99%
“…1,8 An homology model for the structure of the human hemopexin-heme complex based on the structure of the rabbit protein was used to identify several additional, putative binding sites for metal ions on human hemopexin 21 and has led to speculation that hemopexin and the hemopexin-heme complex might 130 On the other hand, at neutral pH Ca 2þ promotes the binding of heme 68 and increases the thermal stability (T m ) of the hemopexin-heme complex. 21 All of these observations, as well as specific ion effects on the dissociation of heme from the hemopexin-heme complex, 57,68,131 suggest a means by which the interaction of the protein with metal ions may promote transfer and binding of heme to hemopexin in blood plasma, release of heme from the hemopexin-heme complex in the endosome, and, as a result, promotion of the known anti-oxidant capacity of hemopexin. Nevertheless, there is no experimental evidence at present that metal ion binding to hemopexin comprises a new functional property of the protein in the transport of metal ions in vivo.…”
Section: Hemopexin As a Metal Ion Binding Proteinmentioning
confidence: 99%